Pengaruh Persepsi Atas Model Pembelajaran Kooperatif dan Kepercayaan Diri Terhadap Kemampuan Komunikasi Matematis - Tamara Primadona; Sumaryoto Sumaryoto; Virgana Virgana (Peneliti.net, 2023)
The aims of the study were to find out: (1) The effect of perceptions on cooperative learning models and joint confidence on the mathematical communication skills of students of State Junior High Schools in Jakarta (2) The effect of perceptions of cooperative learning models on the mathematical communication skills of students of State Junior High Schools in Jakarta (3 ) ) The effect of self-confidence on the mathematical communication skills of students at State Junior High Schools in Jakarta. The population in this study was 751 consisting of 75 Jakarta Public Middle Schools, 189 Jakarta Public Middle Schools, and 271 Jakarta Public Middle Schools. The sample in this study were 76 students who were randomly selected. The method used in this study is a survey with a correlation technique. The results of the study show: (1) There is a significant influence between perceptions of the cooperative learning model and self-confidence on the mathematical communication skills of students at State Junior High Schools in Jakarta. This is evidenced by the value of Sig. = 0.000 <0.05 and Fcount = 24.699. Meanwhile, the magnitude of the perception contribution to the cooperative learning model and self-confidence is indicated by a determination coefficient of 40.4% while the rest is caused by other factors not examined in this study. (2) There is a significant perceived influence of the cooperative learning model on the mathematical communication skills of students at State Junior High Schools in Jakarta. This is evidenced by the value of Sig. 0.000 <0.05 and tcount = 5.402. (3) There is a significant effect of self-confidence on the mathematical communication skills of students at State Junior High Schools in Jakarta. This is evidenced by the value of Sig. = 0.004 <0.05 and tcount = 3.016.